Measuring the linear viscoelastic regime of MCF-7 cells with a monolayer rheometer in the presence of microtubule-active anti-cancer drugs at high concentrations - Lee, Suhyang; Bashir, Khawaja Muhammad Imran; Jung, Dong Hee; Basu, Santanu Kumar; Seo, Gayeon; Cho, Man-Gi; Wierschem, Andreas (Interface Focus, 2022)
The rheological properties of cells have vital functional implications. Depending, for instance, on the life cycle, cells show large cell-to-cell variations making it cumbersome to quantify average viscoelastic properties of cells by single-cell techniques. Microfluidic devices, typically working in the nonlinear viscoelastic range, allow fast analysis of single-cell deformation. Averaging over a large number of cells can also be achieved by studying them in a monolayer between rheometer discs. This technique allows applying well-established rheological standard procedures to cell rheology. It offers further advantages like studying cells in the linear viscoelastic range while quantifying cell vitality. Here, we study the applicability of the technique to rather adverse conditions, like for microtubule-active anti-cancer drugs and for a cell line with large size variation. We found a strong impact of the gap width and of normal forces on the moduli and obtained high vitality levels during the rheological study. To enable studying the impact of microtubule-active drugs on vital cells at concentrations several orders of magnitude beyond the half maximal effective concentration for cytotoxicity, we arrested the cell cycle with hydroxyurea. Irrespective of the high concentrations, we observed no clear impact of the microtubule-active drugs.
CRIS-Team WoS Importer:2022-11-04

Narrow-gap Rheometry: A Novel Method for Measuring Cell Mechanics - Bashir, Khawaja Muhammad Imran; Lee, Suhyang; Jung, Dong Hee; Basu, Santanu Kumar; Cho, Man Gi; Wierschem, Andreas (Cells, 2022)
The viscoelastic properties of a cell cytoskeleton contain abundant information about the state of a cell. Cells show a response to a specific environment or an administered drug through changes in their viscoelastic properties. Studies of single cells have shown that chemical agents that interact with the cytoskeleton can alter mechanical cell properties and suppress mitosis. This envisions using rheological measurements as a non-specific tool for drug development, the pharmacological screening of new drug agents, and to optimize dosage. Although there exists a number of sophisticated methods for studying mechanical properties of single cells, studying concentration dependencies is difficult and cumbersome with these methods: large cell-to-cell variations demand high repetition rates to obtain statistically significant data. Furthermore, method-induced changes in the cell mechanics cannot be excluded when working in a nonlinear viscoelastic range. To address these issues, we not only compared narrow-gap rheometry with commonly used single cell techniques, such as atomic force microscopy and microfluidic-based approaches, but we also compared existing cell monolayer studies used to estimate cell mechanical properties. This review provides insight for whether and how narrow-gap rheometer could be used as an efficient drug screening tool, which could further improve our current understanding of the mechanical issues present in the treatment of human diseases.
CRIS-Team Scopus Importer:2022-07-15
Keywords: cell monolayer; cell rheology; drug screening; human diseases; mechanobiology; mechanophenotyping